DOCTRINE OF THE END TIMES "ESCATOLOGY" - susanti; sarimauli (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Eschatology is generally understood as the Bible's teaching regarding the last days or the period before Jesus returns. The certainty of Christ's second coming which will be accompanied by the events of the resurrection and final judgment, this is also an important doctrine. This article aims to show the importance of this doctrine being taught and understood in the church, especially in the environment. The method used in this research is an interpretative descriptive analysis method of the biblical text.